Babylon In the books of Arab countrymen - al-Sudani , Qasim Jabr Hassan (International Journal of Psychosocial Rehabilitation, 2019)
In this humble research, I dealt with the great city of Babylon, and how it is located in the fourth region, according to the assessment of the Arab countries, from the seven regions that make up the world. And they talked about the reason why Babylon was named so What was the city of Babylon in the past, and what are the conditions and names of its kings? We must talk about (Alexander the Great) who passed through the land of Babylon, built a city in his name, and then died there. Religion was mentioned in ancient Babylon, as well as the agricultural situation in Hilla, the center of the city of Babylon. It talked about the story (Harut and Marut) that was mentioned in the Holy Quran and their location in Babylon